Mechatronics Engineering Department Newsletter - Risalah Issue 1 October 2021 - Mohd Ibrahim, Azhar; Nordin, Nor Hidayati Diyana; Wahid, Azni Nabela; Khan, Md. Raisuddin; Husman, Muhammad Afif; Sophian, Ali; Sidek, Shahrul Na'im; Ghazali, Aimi Shazwani; Mohd Zaki, Hasan Firdaus; Abdul Rahim, Mohammad Najib; Mohammad Abir, Intiaz (2021)
‘MECHATRONICS ENGINEERING DEPARTMENT NEWSLETTER - RISALAH ISSUE 1 is the first bi-yearly newsletter produced by the Mechatronics Engineering Department in Kulliyyah of Engineering, IIUM featuring various events, announcements and information regarding the department including key events, research projects, student activities and success stories in the department.